2015
DOI: 10.1002/2015gl064781
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dispersed ion signatures observed in the Martian magnetosphere by MAVEN

Abstract: Mars Atmosphere and Volatile EvolutioN mission's (MAVEN) high‐cadence measurements reveal the frequent occurrence of ion energy dispersion events inside the Martian magnetosphere. The systematics of observed dispersion signatures suggest time dispersion of a broad source spectrum over a flight distance of a few thousand kilometers and disfavor mechanisms involving spatial dispersion. Pickup of heavy planetary ions in strong variable electric fields provides one potential mechanism that could produce the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
7
19
0
Order By: Relevance
“…Using in situ observations from the NASA Mars Atmosphere and Voltatile EvolutioN (MAVEN) Mars Scout, we show that the impact of compressive magnetosonic waves, from the upstream solar wind, drives linearly polarized, compressive magnetosonic waves in the ionosphere, inducing a localized "ringing" in the induced magnetosphere at the local proton cyclotron frequency. We show that these waves heat and compress the atmosphere and drive time‐dispersed ions as hypothesized by Halekas, McFadden, et al (), likely enhancing ion escape from the upper ionosphere as proposed by Ergun et al (), Lundin et al (), and Dubinin and Fraenz (). Expanding on this single case study to a preliminary survey of the phenomenon, we find that no special conditions are required in the interplanetary magnetic field or solar wind for waves upstream to drive compressive waves in the ionosphere.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Using in situ observations from the NASA Mars Atmosphere and Voltatile EvolutioN (MAVEN) Mars Scout, we show that the impact of compressive magnetosonic waves, from the upstream solar wind, drives linearly polarized, compressive magnetosonic waves in the ionosphere, inducing a localized "ringing" in the induced magnetosphere at the local proton cyclotron frequency. We show that these waves heat and compress the atmosphere and drive time‐dispersed ions as hypothesized by Halekas, McFadden, et al (), likely enhancing ion escape from the upper ionosphere as proposed by Ergun et al (), Lundin et al (), and Dubinin and Fraenz (). Expanding on this single case study to a preliminary survey of the phenomenon, we find that no special conditions are required in the interplanetary magnetic field or solar wind for waves upstream to drive compressive waves in the ionosphere.…”
Section: Introductionsupporting
confidence: 78%
“…However, the spacecraft carried no ion spectrometer and operated in a 400‐km circular science orbit, so this could not be investigated. Recently, Halekas, McFadden, et al () discovered and mapped bursts of time‐dispersed energetic ions at Mars, with frequencies near the upstream proton cyclotron frequency, suggesting that upstream solar wind pressure perturbations may be a driver. Additionally, Fowler et al () found that electric field wave power, whose source was assumed to be within the magnetosheath, penetrates down to ∼200‐km altitude into the dayside upper ionosphere, further suggesting a non‐Martian source of waves in the Martian ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…On the inbound segment MAVEN crossed the induced current sheet, a region surrounded by heated electrons and accelerated planetary ions. On the outbound segment, farther downstream along the flank, the transition from magnetosphere to sheath proves much less distinct, with intermixed solar wind and planetary ions, and highly accelerated heavy ion populations, a few with apparent energy‐time dispersion that may result from nonlocal acceleration of heavy ions [ Halekas et al ., ]. These accelerated ions appear in regions with a wide range of suprathermal electron fluxes, suggesting that they cross magnetic field lines, as expected given their large gyroradii.…”
Section: Maven Solar Wind Ion Analyzer (Swia) Measurements and In‐flimentioning
confidence: 99%
“…These could represent shear‐driven instabilities such as Kelvin‐Helmholtz [ Penz et al ., ] and/or bulk loss of clouds of magnetosphere plasma [ Halekas et al ., ]. Inside the magnetosphere, energy‐time dispersed ions [ Halekas et al ., ] appear throughout the magnetosphere, suggesting acceleration by significant electric fields, possibly associated with the upstream and/or sheath dynamics. On the outbound segment, the IMF rotates away from a radial configuration, and the sheath and upstream region return to a more typical configuration.…”
Section: Maven Solar Wind Ion Analyzer (Swia) Measurements and In‐flimentioning
confidence: 99%
“…The transition between the magnetosheath and the magnetic pileup region has several observational characteristics, which have been identified by different instruments on various spacecraft. One feature is a sharp increase in magnetic field strength coincident with a decrease in field fluctuations, which was observed by Phobos‐2 [e.g., Riedler et al , ], the Mars Global Surveyor (MGS) spacecraft [e.g., Vignes et al , ; Crider et al , ; Bertucci et al , ], and also the Mars Atmosphere and Volatile Evolution (MAVEN) spacecraft [e.g., Jakosky et al , , ; Connerney et al , ; Halekas et al , ; Matsunaga et al , ]. These observations resulted in the names known as the magnetic pileup boundary (MPB) or the induced magnetosphere boundary.…”
Section: Introductionmentioning
confidence: 99%